PERANCANGAN SISTEM PAKAR UNTUK MENGIDENTIFIKASI GANGGUAN PADA TANAMAN JAMBU AIR MENGGUNAKAN METODE CERTAINTY FACTOR - Ahmat Yusuf; Bagus Satrio Waluyo Poetro (Journal of Applied Science and Technology, 2021)
The state of Indonesia, especially in the area of Central Java, is one of the largest producers of water guava. Some farmers rely on the results of guava cultivation as the basis for the family's economy because the guava harvest is quite promising. However, in certain seasons, water guava plants are often attacked by various kinds of pest and disease season disturbances. So that it can reduce crop yields or even cause crop failure. To overcome this problem, fast and precise action is needed so that the guava plant is protected from various kinds of pests and diseases. The method of developing an expert system for disturbance in water guava plants is the best solution in order to identify disturbances in water guava plants as early as possible. The method used in this expert system is the certainty factor method. With this method, several experts are needed to provide data related to disturbances in water guava plants. The expert system for guava plant disorders is designed using a web-based PHP programming language. In designing the knowledge base, which is the core of this system, is made dynamically to make it easier to add new data.